IDENTIFICATION AND CHARACTERIZATION OF THE HUMAN NOL7 GENE PROMOTER - Mankame, Tanmayi P. (2010)
NOL7 is a candidate tumor suppressor gene that localizes to 6p23, a chromosomal region frequently associated with loss of heterozygosity in a number of malignancies including cervical cancer (CC). Re-expression of NOL7 in CC cells suppresses in vivo tumor growth by 95% and alters the angiogenic phenotype by modulating the expression of VEGF and TSP1. Here, we describe the determination of two NOL7 transcriptional start sites (TSS), the cloning of its regulatory promoter region, and the identification of transcription factors that regulate its expression. Using 5′ Rapid amplification of complementary DNA ends (RACE), two transcriptional start sites were identified. Deletion analysis determined that the essential elements required for the optimal promoter activity of NOL7 were 560 bp upstream of its translation start site. In silico analysis suggested that the promoter region contained potential binding sites for the SP1, c-Myc and RXRα transcription factors as well as an overall GC content of greater than 60%. Chromatin immunoprecipitation (ChIP) confirmed that SP1, c-Myc and RXRα bound to the NOL7 promoter region. Finally, we demonstrate that NOL7 expression was positively regulated by c-Myc and RXRα. These results demonstrate that the NOL7 promoter region possesses each of the key elements of a TATA-less promoter. In addition, the positive regulation of NOL7 by c-Myc and RXRα provides additional mechanistic insights into the potential role of NOL7 in CC and other malignancies.